Александр I и Польша: неудачи реформирования в первой трети XIX века - Арутюнян, Л.В. (Культура народов Причерноморья, 2013)
Данная статья представляет собой попытку исследования и анализа опыта создания и существования в составе Российской империи конституционного Царства Польского (1815-1830 гг.). Русско-польские связи имеют тысячелетнюю историю. Первые контакты русских и поляков, зафиксированные летописцами, относятся ко второй половине X века. Статья охватывает события первой четверти XIX в. и комплексно исследует историю конституционного Царства Польского 1815- 1830 гг. в составе Российской империи. Автор рассматривает влияние планов императора Александра I по реформированию государства на форму, в которой произошло включение царства в Российскую империю, историю создания польской конституционной хартии 1815 года. Комплексное рассмотрение истории создания и существования в составе Российской империи конституционного Царства Польского позволило также сделать выводы относительно причин неудачного реформирования и отмены конституционных порядков в царстве. Дана стаття являє собою спробу дослідження й аналізу досвіду створення й існування в складі Російської імперії конституційного Царства Польського (1815-1830 р.). Стаття комплексно досліджує історію конституційного Царства Польського 1815-1830 р. у складі Російської імперії. Автор розглядає вплив планів імператора Олександра I щодо реформування держави на форму, у якій відбулося включення царства в Російську імперію, історію створення польської конституційної хартії 1815 року. Комплексний розгляд історії створення й існування в складі Російської імперії конституційного Царства Польського дозволило так само зробити висновки щодо причин скасування конституційних порядків у царстві й невдалого реформування. This article represents an attempt to research and analyze the experience of creation and existence of the constitutional Kingdom of Poland as a part of the Russian Empire (1815-1830). The Russian-Polish relations have a thousand-year history. The first contacts of Russians and Poles, recorded by chroniclers, were dated to the second half of the X century. The article covers the events of the first quarter of the XIX century and deeply investigates history of the constitutional Kingdom of Poland of 1815-1830 as a part of the Russian Empire. The author considers the influence of state reforming of the Emperor Alexander I on a form in which the Kingdom was included into the Russian Empire, and history of creation of the Polish constitutional charter of 1815. The decree of Alexander I about monetary system in the Kingdom of Poland and the main tendencies of economic, social and political development of the Polish state, fundamental processes of transformation of the Polish society of the first third of the XIX century and its social and political institutes in an interaction with the relevant institutes of the Russian Empire are considered. An attempt is made to give an assessment of results of historical experience of Alexander I reforming with the Kingdom of Poland to find a new form of the solution of some important problems in the Russian Empire. The comprehensive study of history of creation and existence of the constitutional Kingdom of Poland as a part of the Russian Empire allowed us to draw conclusions concerning the reasons of cancellation of constitutional orders in the Kingdom and unsuccessful reforming.